1977
DOI: 10.1111/j.1471-0528.1977.tb12638.x
|View full text |Cite
|
Sign up to set email alerts
|

The EXCRETION OF Γ‐GLUTAMYL TRANSFERASE IN PREGNANCY

Abstract: Summary A cross‐sectional study of γ‐glutamyl transferase (γ‐GT) excretion in 316 healthy pregnant women showed the enzyme excretion (mU per mmol creatinine) was significantly higher than that of a non‐pregnant control group. The increase was apparent before the end of the first trimester and continued thereafter. These changes may be indicative of hypertrophy and/or hyperplasia of the nephron and be part of the overall renal adaptation to normal pregnancy. Even higher levels were recorded in three obstetric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 25 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…In a previous investigation (10) we showed that N-acetyl-ß-jD-glucosaimnidase excretion can be increased solely by fever, without obvious renal äffection, to levels similar tö those obserVed in pregnancy. Thus, N-acetyl-ß-jD-glucosaminidase in urine is a very sensitive test, and the increased excretion of N-acetyl-ß-Z)-glucosaminidase äs well äs other enzymes (11,12) in normal pregnancy probably reflects reversible physiological changes that enhance the rate of enzyme turnover, rather than being due to renal injury. This Interpretation is cönsistent with the normalization of N-acetyl-ß-Z)-glucosaminidase excretion after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous investigation (10) we showed that N-acetyl-ß-jD-glucosaimnidase excretion can be increased solely by fever, without obvious renal äffection, to levels similar tö those obserVed in pregnancy. Thus, N-acetyl-ß-jD-glucosaminidase in urine is a very sensitive test, and the increased excretion of N-acetyl-ß-Z)-glucosaminidase äs well äs other enzymes (11,12) in normal pregnancy probably reflects reversible physiological changes that enhance the rate of enzyme turnover, rather than being due to renal injury. This Interpretation is cönsistent with the normalization of N-acetyl-ß-Z)-glucosaminidase excretion after delivery.…”
Section: Discussionmentioning
confidence: 99%